The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1479973118816497
|View full text |Cite
|
Sign up to set email alerts
|

Inter-day test–retest reliability and feasibility of isokinetic, isometric, and isotonic measurements to assess quadriceps endurance in people with chronic obstructive pulmonary disease: A multicenter study

Abstract: The aims were to determine reliability and feasibility of measurements to assess quadriceps endurance in people with chronic obstructive pulmonary disease. Sixty participants (forced expiratory volume in one second (mean ± standard deviation) 55 ± 18% of predicted, age 67 ± 8 years) were tested in an inter-day, test–retest design. Isokinetic, isometric, and isotonic protocols were performed using a computerized dynamometer. Test–retest relative and absolute reliability was determined via intraclass correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…Participants performed three maximal unilateral isometric knee extensions for five seconds at a knee angle of 60˚, interspersed with 15 seconds of rest. The maximal voluntary contraction was defined as the highest peak torque (Nm) [33] and was both expressed as absolute value as well as related to predicted normal values [34].…”
Section: Measurementsmentioning
confidence: 99%
“…Participants performed three maximal unilateral isometric knee extensions for five seconds at a knee angle of 60˚, interspersed with 15 seconds of rest. The maximal voluntary contraction was defined as the highest peak torque (Nm) [33] and was both expressed as absolute value as well as related to predicted normal values [34].…”
Section: Measurementsmentioning
confidence: 99%
“…Furthermore, the availability of measurement equipment will likely vary between clinical settings and contexts, thus impacting the choice of the assessment strategy. The physiotherapist needs to acknowledge that measurement equipment and assessment strategies are not interchangeable and may provide different information even if the goal of the assessment would be the same [55,57].…”
Section: How To Assess Limb Muscles In Clinical Practicementioning
confidence: 99%
“…Targeting Limb Muscle Dysfunction in COPD http://dx.doi.org/10.5772/intechopen.90815 interventions to interpret findings [57][58][59][60][61], while validity, for example, could be an issue when using simple field tests to provide information on aspects of limb muscle function [62][63][64][65].…”
Section: How To Assess Limb Muscles In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Performance fatigability has been described as "… the magnitude or rate of change in a performance criterion relative to a reference value over a given time of task performance or measure of mechanical output," [22], p.411. Recent investigations [16,27] have examined the inter-day consistency of performance fatigability (i.e., percent decline in peak torque) resulting from various isokinetic fatiguing tasks. For example, Frykholm et al [16] reported low day-to-day consistency in performance fatigability and demonstrated that following 30 unilateral, maximal, concentric, isokinetic (90°/s) leg extension muscle actions there were 39.8% and 41.9% decreases in peak torque on Day 1 and Day 2, respectively.…”
Section: Introductionmentioning
confidence: 99%